Finding out incidence of deafness among neonates at a tertiary care centre of western Rajasthan, India using otoacoustic emission - Gupta, Ashish; Kumar, Vinod (International Journal of Contemporary Pediatrics, 2019)
Background: Newborn hearing screening is conducted to identify suspected hearing loss and not to confirm the presence/absence of hearing loss or define features of the loss. Speech and hearing are interrelated, i.e., a problem with one could mean a problem with the other as speech and language is acquired normally through auditory system. Methods: A descriptive study conducted in the Department of Paediatrics, Dr. S. N. Medical College, Jodhpur, from June 2016 to December 2017. 5000 neonates were screened using otoacoustic emissions (OAE) in 2 stages at birth during 3rd to 7th day and 15-30 days respectively, followed by BERA at 3 months of age. Results: 1.4 infants per thousand infants had hearing loss. Presence of high-risk factors was seen to be associated be associated with hearing loss more than normal infants on screening with distortion product otoacoustic emissions (DPOAE) tests. However, on testing with BERA no such association was seen. Conclusions: 1.4 per 1000 infants had hearing loss. This study has shown that two stage distortion product otoacoustic emissions (DPOAE) hearing screening followed by british educational research association (BERA) to confirm the hearing deficit, can be successfully implemented as new born hearing screening method in a hospital set-up, for early detection of hearing impaired, on a large scale, to achieve the high-quality standard of screening programs in a resource limited and developing nation like India.